A high-dielectric aluminum-doped perovskite structure high-entropy microwave dielectric ceramic and preparation method thereof

By introducing high entropy concepts and Al3+ doping into perovskite ceramics, dielectric performance is regulated, and the problems of poor dielectric loss and temperature stability of existing materials under high dielectric constant are solved, and microwave dielectric ceramics with high dielectric constant, low dielectric loss and good temperature stability are achieved.

CN117229056BActive Publication Date: 2025-04-29TAIYUAN UNIVERSITY OF TECHNOLOGY
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202311168651.7
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-09-12
Publication Date
2025-04-29
Estimated Expiration
2043-09-12

AI Technical Summary

Technical Problem

In the process of pursuing high dielectric constants, existing microwave dielectric ceramic materials are difficult to take into account low dielectric loss and temperature stability, resulting in poor performance under high frequency and temperature changes.

Method used

Adopting the high-entropy concept, the high-entropy microwave dielectric ceramics with excellent functions are synthesized by doping Al3+ ions to replace Ti4+, and dielectric performance is regulated, and process parameters such as sintering temperature, reaction time and doping content are controlled.

Benefits of technology

The dielectric constant between 74-91 is achieved, the dielectric loss is between 0.001-0.002, and the resonant frequency temperature coefficient is between 175-217ppm/℃, which significantly improves the microwave dielectric performance of the material.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN117229056B_ABST
    Figure CN117229056B_ABST
Patent Text Reader

Abstract

The present invention discloses a high-dielectric aluminum-doped perovskite-structured high-entropy microwave dielectric ceramic and a preparation method thereof, belonging to the technical field of ceramic materials in the communication field. The chemical general formula of the high-entropy microwave dielectric ceramic is (Zn 1 / 6 Ba 1 / 6 Ca 1 / 6 Sr 1 / 6 La 1 / 3 )Ti 1‑ x Al x O3, where: x = 0 - 0.1. Based on the unique effect of high entropy, the present invention first introduces the high-entropy concept into the perovskite-structured microwave dielectric ceramic to attempt to regulate the dielectric properties, and successfully synthesizes the aluminum-doped high-entropy microwave dielectric ceramic by controlling process parameters such as sintering temperature, reaction time, and doping content. Its dielectric constant is 74 - 91, the dielectric loss is 0.001 - 0.002, and the temperature coefficient of resonant frequency is 175 - 217 ppm / °C, obtaining excellent microwave dielectric properties. The high-dielectric microwave dielectric ceramic obtained by the present invention is expected to be applied to mobile terminals and communication base stations, etc.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of ceramic materials in the field of communications, and in particular relates to a high-dielectric aluminum-doped perovskite structure high-entropy microwave dielectric ceramic and a preparation method thereof. Background Art

[0002] In recent years, mobile communication technologies such as satellite communication, positioning navigation, and 5G technology have developed rapidly. Microwave dielectric ceramics, as functional materials in microwave frequency band circuits, are widely used in car phones, satellite live TV, satellite communications, medical diagnostic instruments, etc. At the same time, as a key material for microwave components, it has attracted the attention of more and more researchers, and performance requirements such as high frequency, integration, miniaturization, and intelligence have been proposed for microwave dielectric ceramic materials. The size of microwave dielectric ceramics is inversely proportional to its dielectric constant, so the larger the dielectric constant, the more conducive to product miniaturization. Materials with smaller dielectric constants have been well applied at present, but for high dielectric constants, there is a basic conflict at the basic physical level of materials - the atomic polarization process required to achieve high dielectric constants also inevitably causes dielectric loss and temperature dependence of dielectric constants. Therefore, the research and development of microwave dielectric ceramics with high dielectric constants and suitable performance has become an urgent need of the electronics market, and the exploration of new systems is still in its early stages.

[0003] High entropy ceramics are a new type of ceramic material after high entropy alloys. Due to their unique effects, they have attracted a large number of scholars. High entropy perovskite oxides have been widely studied because they allow for a large tolerance factor and a rich variety of crystal structures. The selectivity of high entropy components, the adjustability of component concentrations, and the diversity of performance provide a new way to regulate the performance of microwave dielectric ceramics. Currently, high entropy perovskite ceramics are all concentrated in thermoelectrics, ferroelectrics, and energy storage. No one has yet explored the research on high dielectric high entropy ceramics in the field of microwave dielectrics. Summary of the invention

[0004] In view of the above research background, the purpose of the present invention is to apply the high entropy concept to perovskite ceramics for the first time, and try to explore a microwave dielectric ceramic with a high dielectric constant. Therefore, the present invention proposes a high dielectric constant aluminum-doped perovskite structure high entropy microwave dielectric ceramic and a preparation method thereof.

[0005] To achieve the above object, the present invention provides the following technical solutions:

[0006] A high-dielectric aluminum-doped perovskite structure high-entropy microwave dielectric ceramic, the chemical general formula of the high-entropy microwave dielectric ceramic is (Zn 1 / 6 Ba 1 / 6 Ca 1 / 6 Sr 1 / 6 La 1 / 3 )Ti 1-xAl x O 3 , wherein: x = 0-0.1. x may preferably be 0, 0.02, 0.04, 0.06, 0.08, 0.1.

[0007] The present invention also provides a method for preparing the high-dielectric aluminum-doped perovskite structure high-entropy microwave dielectric ceramic, comprising the following steps:

[0008] 1) Weigh the raw materials ZnO and CaCO according to the stoichiometric ratio 3 、BaCO 3 、SrO、La 2 O 3 、TiO 2 and Al 2 O 3 , adding a solvent and then ball milling to obtain a mixed slurry;

[0009] 2) drying the mixed slurry, pre-calcining the obtained powder, performing secondary ball milling, and further drying to obtain dry powder;

[0010] 3) granulating the dried powder and sequentially placing it into a hydraulic press and a cold isostatic press to press it into a ceramic green body;

[0011] 4) Sintering the ceramic green body in a protective gas atmosphere to obtain (Zn 1 / 6 Ba 1 / 6 Ca 1 / 6 Sr 1 / 6 La 1 / 3 )Ti 1-x Al x O 3 A high entropy ceramic block is mechanically processed, cleaned and dried to obtain a high-dielectric aluminum-doped perovskite structure high-entropy microwave dielectric ceramic.

[0012] Furthermore, the raw materials ZnO, CaCO 3 、BaCO 3 、SrO、La 2 O 3 、TiO 2 and Al 2 O 3 The purity is greater than 99.5%.

[0013] Furthermore, the raw materials ZnO, CaCO 3 、BaCO 3 , SrO and La 2 O 3 The molar ratio of Zn, Ba, Ca, Sr and La elements is 1:1:1:1:2.

[0014] Furthermore, in the ball milling process of step 1) and step 2), the grinding medium is agate balls, the organic solvent is ethanol, a star ball mill is used, the ball-to-material ratio is 6:1, the ball milling time is 8 hours, the rotation speed is 300 r / min, and there is a 10-minute rest period after every 30 minutes of ball milling.

[0015] Furthermore, the pre-sintering in step 2) refers to pre-sintering at 1000° C. for 2 hours. The drying refers to drying at 80° C. for 10 hours.

[0016] Furthermore, in step 3), the parameters set for the hydraulic press are: pressure 150-200 MPa, pressure holding time 3-5 min; the parameters set for the cold isostatic press are: pressure 250-300 MPa, pressure holding time 15-20 min. The diameter of the mold used in the pressing process is 10 mm.

[0017] Furthermore, the binder used in the granulation process of step 3) is a 5 wt % PVA aqueous solution, and the amount of the binder is 8% of the volume of the dry powder.

[0018] Furthermore, the sintering in step 4) refers to keeping the temperature at 1325-1400° C. for 4 hours. The mechanical processing refers to processing the high entropy ceramic block into a sample with a size of 5 mm in height and 8.5 mm in diameter.

[0019] The present invention is based on the CM theory and adopts Al with low ion polarizability to 3+ Ti with higher ion polarizability 4 + While maintaining a high dielectric constant and low dielectric loss, the resonant frequency temperature coefficient of traditional perovskites is reduced, and the grain size fitting is used to prove the influence on dielectric loss.

[0020] Compared with the prior art, the present invention has the following advantages and technical effects:

[0021] Based on the unique effect of high entropy, the present invention introduces the concept of high entropy into perovskite structure microwave dielectric ceramics for the first time to try to regulate dielectric properties. By controlling process parameters such as sintering temperature, reaction time and doping content, aluminum-doped high entropy microwave dielectric ceramics are successfully synthesized. Its dielectric constant is 74-91, dielectric loss is 0.001-0.002, and resonant frequency temperature coefficient is 175-217ppm / ℃, achieving excellent microwave dielectric properties. The high dielectric microwave dielectric ceramics obtained by the present invention are expected to be used in mobile terminals and communication base stations. BRIEF DESCRIPTION OF THE DRAWINGS

[0022] The drawings constituting a part of the present application are used to provide a further understanding of the present application. The illustrative embodiments and descriptions of the present application are used to explain the present application and do not constitute an improper limitation on the present application. In the drawings:

[0023] Figure 1 X-ray diffraction pattern of the high dielectric aluminum-doped perovskite structure high entropy microwave dielectric ceramic prepared in Examples 1-6 of the present invention;

[0024] Figure 2 The SEM microstructure diagrams of the high-dielectric aluminum-doped perovskite structure high-entropy microwave dielectric ceramics prepared in Examples 1-6 of the present invention; wherein (a) is Example 1, (b) is Example 2, (c) is Example 3, (d) is Example 4, (e) is Example 5, and (f) is Example 6;

[0025] Figure 3 The grain size frequency distribution histograms of the high dielectric aluminum-doped perovskite structure high entropy microwave dielectric ceramics prepared in Examples 1-6 of the present invention; wherein (a) is Example 1, (b) is Example 2, (c) is Example 3, (d) is Example 4, (e) is Example 5, and (f) is Example 6;

[0026] Figure 4 The dielectric constant diagram of the high dielectric aluminum-doped perovskite structure high entropy microwave dielectric ceramics prepared in Examples 1-6 of the present invention;

[0027] Figure 5 Qf diagram of high dielectric aluminum-doped perovskite structure high entropy microwave dielectric ceramics prepared in Examples 1-6 of the present invention;

[0028] Figure 6 This is a diagram of the resonant frequency temperature coefficient of the high dielectric aluminum-doped perovskite structure high entropy microwave dielectric ceramics prepared in Examples 1-6 of the present invention. DETAILED DESCRIPTION

[0029] Various exemplary embodiments of the present invention will now be described in detail. This detailed description should not be considered as limiting the present invention, but should be understood as a more detailed description of certain aspects, features, and embodiments of the present invention.

[0030] It should be understood that the terms described in the present invention are only for describing special embodiments and are not intended to limit the present invention. In addition, for the numerical range in the present invention, it should be understood that each intermediate value between the upper and lower limits of the scope is also specifically disclosed. Each smaller range between the intermediate value in any stated value or stated range and any other stated value or intermediate value in the described range is also included in the present invention. The upper and lower limits of these smaller ranges can be independently included or excluded in the scope.

[0031] Unless otherwise indicated, all technical and scientific terms used herein have the same meanings as those generally understood by those skilled in the art. Although the present invention describes only preferred methods and materials, any methods and materials similar or equivalent to those described herein may also be used in the implementation or testing of the present invention. All documents mentioned in this specification are incorporated by reference to disclose and describe the methods and / or materials associated with the documents. In the event of a conflict with any incorporated document, the content of this specification shall prevail.

[0032] It will be apparent to those skilled in the art that various modifications and variations may be made to the specific embodiments of the present invention description without departing from the scope or spirit of the present invention. Other embodiments derived from the present invention description will be apparent to those skilled in the art. The present application description and examples are exemplary only.

[0033] The words “include,” “including,” “have,” “contain,” etc. used in this document are open-ended terms, meaning including but not limited to.

[0034] The "room temperature" mentioned in the present invention is 25±2°C unless otherwise specified.

[0035] The raw materials used in the following examples of the present invention are all commercially available.

[0036] The present invention provides a high-dielectric aluminum-doped perovskite structure high-entropy microwave dielectric ceramic, the chemical general formula of which is (Zn 1 / 6 Ba 1 / 6 Ca 1 / 6 Sr 1 / 6 La 1 / 3 )Ti 1-x Al x O 3 , wherein: x = 0-0.1. x may preferably be 0, 0.02, 0.04, 0.06, 0.08, 0.1.

[0037] The present invention also provides a method for preparing the high-dielectric aluminum-doped perovskite structure high-entropy microwave dielectric ceramic, comprising the following steps:

[0038] Step (1): ZnO, CaCO 3 、BaCO 3 、SrO、La 2 O 3 、TiO 2 、Al 2 O 3 The original powder was divided into target product (Zn 1 / 6 Ba 1 / 6 Ca 1 / 6 Sr1 / 6 La 1 / 3 )Ti 1-x Al x O 3 The ingredients are prepared in a stoichiometric ratio of (x=0, 0.02, 0.04, 0.06, 0.08, 0.1), wherein the molar ratio of the five metal elements Zn, Ba, Ca, Sr, and La is 1:1:1:1:2, and a solvent is added to perform ball milling in a planetary ball mill to obtain a mixed slurry;

[0039] Step (2): placing the mixed slurry obtained in step (1) in an electric heated air drying oven for drying to obtain a dry powder;

[0040] Step (3): pre-calculating the dry powder obtained in step (2), performing secondary ball milling, and then repeating the operation of step (2);

[0041] Step (4): granulating the dry powder obtained in step (3) and sequentially placing it in a hydraulic press and a cold isostatic press to obtain a ceramic green body; the granulation in this step refers to mixing the dry powder with a binder PVA;

[0042] Step (5): Place the ceramic green body obtained in step (4) in an atmosphere sintering furnace for sintering to obtain (Zn 1 / 6 Ba 1 / 6 Ca 1 / 6 Sr 1 / 6 La 1 / 3 )Ti 1-x Al x O 3 A high entropy ceramic block is mechanically processed, cleaned and dried to obtain a high-dielectric aluminum-doped perovskite structure high-entropy microwave dielectric ceramic.

[0043] In the following embodiment step (1) of the present invention, the raw materials ZnO, CaCO 3 、BaCO 3 、SrO、La 2 O 3 、TiO 2 and Al 2 O 3 The purity is greater than 99.5%.

[0044] In the ball milling process of step (1) and step (3) in some preferred embodiments of the present invention, the grinding medium is agate balls, the organic solvent is ethanol, a star ball mill is used, the ball-to-material ratio is 6:1, the ball milling time is 8 hours, the rotation speed is 300 r / min, and a rest period of 10 minutes is taken after every 30 minutes of ball milling.

[0045] In some preferred embodiments of the present invention, in step (2) and step (3), the drying refers to drying at 80° C. for 10 hours.

[0046] In step (3) of some preferred embodiments of the present invention, the pre-firing refers to pre-firing at 1000° C. for 2 hours.

[0047] In step (4) of some preferred embodiments of the present invention, the parameters set for the hydraulic press are: pressure 150-200MPa, preferably 150MPa, and pressure holding time 3-5min, preferably 3min; the parameters set for the cold isostatic press are: pressure 250-300MPa, preferably 250MPa, and pressure holding time 15-20min, preferably 15min. The diameter of the mold used in the pressing process is 10mm. The binder used in the granulation process is a 5wt% PVA aqueous solution, and the amount of the binder is 8% of the volume of the dry powder.

[0048] In step (5) of some preferred embodiments of the present invention, the sintering refers to: first, keeping the temperature at 500°C for 2 hours, then heating the temperature to 1200°C at a rate of 5°C / min, heating the green body to 1325-1400°C at a rate of 2°C / min, and keeping the temperature for 4 hours; after the insulation, cooling the green body to 1200°C at a rate of 2°C / min, cooling the green body to 500°C at a rate of 5°C / min, and then cooling the green body to room temperature with the furnace. The mechanical processing refers to processing the high entropy ceramic block into a sample with a size of 5 mm in height and 8.5 mm in diameter.

[0049] The present invention is based on the fact that traditional perovskites have high dielectric constants, and attempts to introduce the concept of high entropy to explore high dielectric microwave dielectric ceramics, which will be further explained below.

[0050] Example 1

[0051] Step (1): ZnO, CaCO 3 、BaCO 3 、SrO、La 2 O 3 、TiO 2 、Al 2 O 3 The original powder was divided into target product (Zn 1 / 6 Ba 1 / 6 Ca 1 / 6 Sr 1 / 6 La 1 / 3 )Ti 1-x Al x O 3 (x=0, that is, the chemical formula is (Zn 1 / 6 Ba 1 / 6 Ca 1 / 6 Sr 1 / 6 La1 / 3 )TiO 3 ) was prepared in a stoichiometric ratio, wherein the molar ratio of the five metal elements Zn, Ba, Ca, Sr and La was 1:1:1:1:2, the powders were mixed and placed in a planetary ball mill, agate balls were used as grinding media, ethanol was used as a dispersant for ball milling, and the ball-to-material ratio was 6:1. The planetary ball mill was operated alternately in forward and reverse directions at a speed of 300 r / min, the alternating operation time was 30 min, the alternating operation interval was 10 min, and the alternating operation was repeated 13 times;

[0052] Step (2): placing the mixed slurry obtained by ball milling in an electric heated air drying oven and drying at 80° C. for 10 h;

[0053] Step (3): placing the dried powder in a muffle furnace, heating the temperature to 1000°C at a heating rate of 5°C / min for pre-sintering, keeping the temperature for 2 hours, and then cooling the powder to room temperature in the furnace;

[0054] Step (4): placing the pre-calcined powder in a planetary ball mill, running it at a speed of 300 r / min for 8 hours, with an alternating running time of 30 minutes and a stop time of 10 minutes between alternating running, and then drying it at 80° C. for 10 hours to obtain a dry powder;

[0055] Step (5): Place the dry powder in an agate mortar and add 5 wt% PVA aqueous solution while grinding until the powder and PVA are evenly mixed. The amount of adhesive used is 8% of the volume of the dry powder;

[0056] Step (6): placing the treated high entropy ceramic powder in a mold with a diameter of 10 mm, applying a pressure of 150 MPa using a hydraulic press, and maintaining the pressure for 3 minutes; then placing the powder in a cold isostatic press, increasing the pressure to 250 MPa at 50 MPa / min, maintaining the pressure for 15 minutes, and then reducing the pressure to 0 MPa at 50 MPa / min to obtain a ceramic green body;

[0057] Step (7): Place the ceramic green body in a muffle furnace, raise the temperature to 500°C at a rate of 2°C / min and keep it for 2 hours to remove binder, then raise the temperature to 1200°C at a rate of 5°C / min, raise the temperature of the green body to 1400°C at a rate of 2°C / min, and keep it for 4 hours; after the insulation, cool it to 1200°C at a rate of 2°C / min, cool it to 500°C at a rate of 5°C / min, and then cool it with the furnace. Use 200-1200 mesh sandpaper (first use 200 mesh sandpaper for coarse grinding, then use 800 mesh sandpaper for fine grinding, and finally use 1200 mesh sandpaper for polishing) to grind and clean the ceramic block. Finally, a high-dielectric aluminum-doped perovskite structure high-entropy microwave dielectric ceramic is obtained, denoted as (Zn 1 / 6 Ba 1 / 6 Ca 1 / 6 Sr1 / 6 La 1 / 3 )TiO 3 (exist Figure 1 Marked as ZBCSL1400℃).

[0058] The high-dielectric aluminum-doped perovskite structure high-entropy microwave dielectric ceramic prepared in this embodiment has a dielectric constant of 84.2, a dielectric loss of 0.0018 (@4.14GHz), and a resonant frequency temperature coefficient of 217ppm / °C.

[0059] Example 2

[0060] Step (1): ZnO, CaCO 3 、BaCO 3 、SrO、La 2 O 3 、TiO 2 、Al 2 O 3 The original powder was divided into target product (Zn 1 / 6 Ba 1 / 6 Ca 1 / 6 Sr 1 / 6 La 1 / 3 )Ti 1-x Al x O 3 The ingredients are prepared in a stoichiometric ratio of (x=0.02), wherein the molar ratio of the five metal elements Zn, Ba, Ca, Sr, and La is 1:1:1:1:2, and the powders are mixed and placed in a planetary ball mill, with agate balls as grinding media and ethanol as dispersant for ball milling, with a ball-to-material ratio of 6:1. The planetary ball mill rotates alternately in forward and reverse directions at a speed of 300r / min, the alternating operation time is 30min, the alternating operation interval is 10min, and the alternating operation is performed 13 times;

[0061] Steps (2) to (7) are the same as those in Example 1. The obtained high dielectric aluminum-doped perovskite structure high entropy microwave dielectric ceramic is denoted as (Zn 1 / 6 Ba 1 / 6 Ca 1 / 6 Sr 1 / 6 La 1 / 3 )Ti 0.98 Al 0.02 O 3 .

[0062] The high-dielectric aluminum-doped perovskite structure high-entropy microwave dielectric ceramic prepared in this embodiment has a dielectric constant of 90.82, a dielectric loss of 0.0013 (@3.89GHz), and a resonant frequency temperature coefficient of 199ppm / °C.

[0063] Example 3

[0064] Step (1): ZnO, CaCO 3 、BaCO 3 、SrO、La 2 O 3 、TiO 2 、Al 2 O 3 The original powder was divided into target product (Zn 1 / 6 Ba 1 / 6 Ca 1 / 6 Sr 1 / 6 La 1 / 3 )Ti 1-x Al x O 3 The ingredients are prepared in a stoichiometric ratio of (x=0.04), wherein the molar ratio of the five metal elements Zn, Ba, Ca, Sr, and La is 1:1:1:1:2, and the powders are mixed and placed in a planetary ball mill, with agate balls as grinding media and ethanol as dispersant for ball milling, with a ball-to-material ratio of 6:1. The planetary ball mill rotates alternately in forward and reverse directions at a speed of 300r / min, the alternating operation time is 30min, the alternating operation interval is 10min, and the alternating operation is performed 13 times;

[0065] Steps (2) to (7) are the same as those in Example 1. The obtained high dielectric aluminum-doped perovskite structure high entropy microwave dielectric ceramic is denoted as (Zn 1 / 6 Ba 1 / 6 Ca 1 / 6 Sr 1 / 6 La 1 / 3 )Ti 0.96 Al 0.04 O 3 .

[0066] The high-dielectric aluminum-doped perovskite structure high-entropy microwave dielectric ceramic prepared in this embodiment has a dielectric constant of 85.018, a dielectric loss of 0.0013 (@4.02GHz), and a resonant frequency temperature coefficient of 196ppm / °C.

[0067] Example 4

[0068] Step (1): ZnO, CaCO 3 、BaCO 3 、SrO、La 2 O 3 、TiO 2 、Al 2 O 3 The original powder was divided into target product (Zn 1 / 6 Ba 1 / 6 Ca 1 / 6 Sr 1 / 6 La 1 / 3)Ti 1-x Al x O 3 The ingredients are prepared in a stoichiometric ratio of (x=0.06), wherein the molar ratio of the five metal elements Zn, Ba, Ca, Sr, and La is 1:1:1:1:2, and the powders are mixed and placed in a planetary ball mill, with agate balls as grinding media and ethanol as dispersant for ball milling, with a ball-to-material ratio of 6:1. The planetary ball mill is operated alternately in forward and reverse directions at a speed of 300r / min, the alternating operation time is 30min, the alternating operation interval is 10min, and the alternating operation is performed 13 times;

[0069] Steps (2) to (7) are the same as those in Example 1. The obtained high dielectric aluminum-doped perovskite structure high entropy microwave dielectric ceramic is denoted as (Zn 1 / 6 Ba 1 / 6 Ca 1 / 6 Sr 1 / 6 La 1 / 3 )Ti 0.94 Al 0.06 O 3 .

[0070] The high-dielectric aluminum-doped perovskite structure high-entropy microwave dielectric ceramic prepared in this embodiment has a dielectric constant of 78.42, a dielectric loss of 0.0014 (@4.2GHz), and a resonant frequency temperature coefficient of 194ppm / °C.

[0071] Example 5

[0072] Step (1): ZnO, CaCO 3 、BaCO 3 、SrO、La 2 O 3 、TiO 2 、Al 2 O 3 The original powder was divided into target product (Zn 1 / 6 Ba 1 / 6 Ca 1 / 6 Sr 1 / 6 La 1 / 3 )Ti 1-x Al x O 3 The ingredients are prepared in a stoichiometric ratio of (x=0.08), wherein the molar ratio of the five metal elements Zn, Ba, Ca, Sr, and La is 1:1:1:1:2, and the powders are mixed and placed in a planetary ball mill, with agate balls as grinding media and ethanol as dispersant for ball milling, with a ball-to-material ratio of 6:1. The planetary ball mill rotates alternately in forward and reverse directions at a speed of 300r / min, the alternating operation time is 30min, the alternating operation interval is 10min, and the alternating operation is performed 13 times;

[0073] Steps (2) to (7) are the same as those in Example 1. The obtained high dielectric aluminum-doped perovskite structure high entropy microwave dielectric ceramic is denoted as (Zn 1 / 6 Ba 1 / 6 Ca 1 / 6 Sr 1 / 6 La 1 / 3 )Ti 0.92 Al 0.08 O 3 .

[0074] The high-dielectric aluminum-doped perovskite structure high-entropy microwave dielectric ceramic prepared in this embodiment has a dielectric constant of 74.46, a dielectric loss of 0.0013 (@4.31 GHz), and a resonant frequency temperature coefficient of 184 ppm / °C.

[0075] Example 6

[0076] Step (1): ZnO, CaCO 3 、BaCO 3 、SrO、La 2 O 3 、TiO 2 、Al 2 O 3 The original powder was divided into target product (Zn 1 / 6 Ba 1 / 6 Ca 1 / 6 Sr 1 / 6 La 1 / 3 )Ti 1-x Al x O 3 The ingredients are prepared in a stoichiometric ratio of (x=0.1), wherein the molar ratio of the five metal elements Zn, Ba, Ca, Sr, and La is 1:1:1:1:2, and the powders are mixed and placed in a planetary ball mill, with agate balls as grinding media and ethanol as dispersant for ball milling, with a ball-to-material ratio of 6:1. The planetary ball mill rotates alternately in forward and reverse directions at a speed of 300r / min, the alternating operation time is 30min, the alternating operation interval is 10min, and the alternating operation is performed 13 times;

[0077] Steps (2) to (7) are the same as those in Example 1. The obtained high dielectric aluminum-doped perovskite structure high entropy microwave dielectric ceramic is denoted as (Zn 1 / 6 Ba 1 / 6 Ca 1 / 6 Sr 1 / 6 La 1 / 3 )Ti 0.9 Al 0.1 O 3 .

[0078] The high-dielectric aluminum-doped perovskite structure high-entropy microwave dielectric ceramic prepared in this embodiment has a dielectric constant of 75.26, a dielectric loss of 0.0011 (@4.25GHz), and a resonant frequency temperature coefficient of 175ppm / °C.

[0079] Figure 1 X-ray diffraction patterns of high dielectric aluminum-doped perovskite structure high entropy microwave dielectric ceramics prepared in Examples 1-6 of the present invention, wherein x=0, 0.02, 0.04, 0.06, 0.08, 0.1; Figure 1 It can be seen that all synthesized high entropy ceramics have perovskite structure and no second phase is generated.

[0080] Figure 2 The SEM microstructure of the high-dielectric aluminum-doped perovskite structure high-entropy microwave dielectric ceramic prepared in Examples 1-6 of the present invention; Figure 2 It can be seen that the synthesized high-entropy ceramics have clear grain boundaries, relatively uniform sizes and high density.

[0081] Figure 3 The grain size frequency distribution histogram of the high dielectric aluminum-doped perovskite structure high entropy microwave dielectric ceramics prepared in Examples 1-6 of the present invention is shown in FIG. Figure 3 It can be seen that the grain size of the synthesized high entropy ceramics gradually decreases with the increase of Al content.

[0082] Figure 4 The dielectric constant diagram of the high dielectric constant aluminum-doped perovskite structure high entropy microwave dielectric ceramics prepared in Examples 1-6 of the present invention is shown in FIG. Figure 4 It can be seen that the dielectric constants of the synthesized high entropy ceramics are all greater than 70.

[0083] Figure 5 Qf diagram of high dielectric aluminum-doped perovskite structure high entropy microwave dielectric ceramics prepared in Examples 1-6 of the present invention, from Figure 5 It can be seen that the dielectric loss of the synthesized high entropy ceramics gradually decreases with the increase of Al content.

[0084] Figure 6 The resonant frequency temperature coefficient diagram of the high dielectric aluminum-doped perovskite structure high entropy microwave dielectric ceramics prepared in Examples 1-6 of the present invention is shown in FIG. Figure 6 It can be seen that with the increase of Al content, the temperature coefficient of resonant frequency gradually decreases.

[0085] It can be illustrated by the above embodiments and drawings that the dielectric constants of the high-dielectric aluminum-doped perovskite structured high-entropy microwave dielectric ceramics synthesized by the present invention are all greater than 70, belonging to the range of high-dielectric microwave dielectric ceramics, and have a medium quality factor. Compared with traditional perovskites, the resonant frequency temperature coefficient is greatly reduced, and there is still room for improvement, and it is expected to be applied to mobile terminals and communication base stations, etc.

[0086] Example 7

[0087] Step (1) to step (6) are the same as in Example 1.

[0088] Step (7): Place the ceramic green body in a muffle furnace, raise the temperature to 500°C at a rate of 2°C / min and keep it for 2 hours to remove binder, then raise the temperature to 1200°C at a rate of 5°C / min, raise the temperature of the green body to 1350°C at a rate of 2°C / min, and keep it for 6 hours; after the insulation, cool it to 1200°C at a rate of 2°C / min, cool it to 500°C at a rate of 5°C / min, and then cool it with the furnace. First use 200 mesh sandpaper for coarse grinding, then use 800 mesh sandpaper for fine grinding, and finally polish with 1200 mesh sandpaper, and then clean it. The high dielectric aluminum-doped perovskite structure high entropy microwave dielectric ceramic finally obtained is denoted as (Zn 1 / 6 Ba 1 / 6 Ca 1 / 6 Sr 1 / 6 La 1 / 3 )TiO 3 .

[0089] The high-dielectric aluminum-doped perovskite structure high-entropy microwave dielectric ceramic prepared in this embodiment has a dielectric constant of 78.937, a dielectric loss of 0.0024 (@4.199GHz), and a resonant frequency temperature coefficient of 229ppm / °C.

[0090] Comparative Example 1

[0091] Same as Example 6, except that Al 2 O 3 Replaced with NiO.

[0092] The nickel-doped perovskite structured high-entropy microwave dielectric ceramic prepared in this comparative example has a dielectric constant of 68.884, a dielectric loss of 0.0018 (@4.527 GHz), and a resonant frequency temperature coefficient of 189 ppm / °C.

[0093] Comparative Example 2

[0094] Same as Example 6, except that Al 2 O 3 Replaced by Co 3 O 4 .

[0095] The high-dielectric aluminum-doped perovskite structure high-entropy microwave dielectric ceramic prepared in this comparative example has a dielectric constant of 73.077, a dielectric loss of 0.0019 (@4.389GHz), and a resonant frequency temperature coefficient of 217ppm / °C.

[0096] The above are only preferred specific implementations of the present application, but the protection scope of the present application is not limited thereto. Any changes or substitutions that can be easily thought of by a person skilled in the art within the technical scope disclosed in the present application should be included in the protection scope of the present application. Therefore, the protection scope of the present application should be based on the protection scope of the claims.

Claims

1. A high-dielectric aluminum-doped perovskite structure high-entropy microwave dielectric ceramic, characterized in that: The chemical formula of the high entropy microwave dielectric ceramic is (Zn 1 / 6 Ba 1 / 6 Ca 1 / 6 Sr 1 / 6 La 1 / 3 )Ti 1-x Al x O3, where: x = 0-0.

1.

2. A method for preparing a high-dielectric aluminum-doped perovskite structure high-entropy microwave dielectric ceramic as claimed in claim 1, characterized in that: The following steps are involved: Raw materials ZnO, CaCO3, BaCO3, SrO, La2O3, TiO2 and Al2O3 are weighed according to the stoichiometric ratio, and a solvent is added and ball-milled to obtain a mixed slurry; The mixed slurry is dried, the obtained powder is pre-calcined, ball-milled for a second time, and further dried to obtain a dry powder; The dried powder is granulated and then put into a hydraulic press and a cold isostatic press to be pressed into a ceramic green body; The ceramic green body is sintered in a protective gas atmosphere to obtain a high-dielectric aluminum-doped perovskite structure high-entropy microwave dielectric ceramic.

3. The method for preparing the high-dielectric aluminum-doped perovskite structure high-entropy microwave dielectric ceramic according to claim 2, characterized in that: The purity of the raw materials ZnO, CaCO3, BaCO3, SrO, La2O3, TiO2 and Al2O3 is greater than 99.5%.

4. The method for preparing the high-dielectric aluminum-doped perovskite structure high-entropy microwave dielectric ceramic according to claim 2, characterized in that: Each ball milling process adopts forward and reverse alternating interval operation, wherein the ball-to-material ratio is 6:1, the ball milling time is 8 hours, the rotation speed is 300r / min, the alternating operation time is 30 minutes, and the interval shutdown is 10 minutes.

5. The method for preparing the high-dielectric aluminum-doped perovskite structure high-entropy microwave dielectric ceramic according to claim 2, characterized in that: The pre-sintering refers to pre-sintering at 1000° C. for 2 hours.

6. The method for preparing the high-dielectric aluminum-doped perovskite structure high-entropy microwave dielectric ceramic according to claim 2, characterized in that: The parameters set for the hydraulic press are: pressure 150-200MPa, and pressure holding time 3-5min; the parameters set for the cold isostatic press are: pressure 250-300MPa, and pressure holding time 15-20min.

7. The method for preparing the high-dielectric aluminum-doped perovskite structure high-entropy microwave dielectric ceramic according to claim 2, characterized in that: The binder used in the granulation process is a 5 wt % PVA aqueous solution, and the amount of the binder is 8% of the volume of the dry powder.

8. The method for preparing the high-dielectric aluminum-doped perovskite structure high-entropy microwave dielectric ceramic according to claim 2, characterized in that: The sintering refers to keeping the temperature at 1325-1400° C. for 4 hours.

Citation Information

Patent Citations

  • A new class of high-entropy perovskite ceramics with robust ferroelectricity

    AU2021102229A4

  • Sn-doped high-entropy perovskite oxide ceramic material with high power density, and preparation method thereof

    CN111039672A